FRI0714-HPR A PILOT NURSE-LED TELEPHONE TRIAGE LINE OF PATIENTS WITH RHEUMATOLOGIC RARE DISEASES IN A TERTIARY CENTER. (June 2019) - Kis, Eva; Ciursa, Gabriela; Jurjiu, Bianca; Filipescu, Ileana; Muntean, Laura; Simon, Siao-Pin; Rednic, Simona; Damian, Laura
Abstract : Background: The general rheumatology outpatient clinics are facing an increasing workload. The patients already in evidence with rare or complex inflammatory diseases, such as inflammatory myopathies, systemic lupus erythematosus, mixed connective tissue diseases, systemic sclerosis, Sjogren's syndrome, relapsing polychondritis, systemic vasculitides and other collagen-vascular diseases are being scheduled for outpatient or hospital assessment at the current visit. However the patients may need earlier appointments, given the possibility of flares or other issues. Objectives: To assess the role of a nurse-led telephonic triage line in patients with rare rheumatologic diseases. Methods: The nurses accepting to be enrolled in the programme answered the phone for the patients already in the department's and their follow-up with rare or complex inflammatory rheumatic diseases. A 2-hours training programme with attending physicians was completed. Respecting confidentiality agreement regulations, the calls were registered with the nume, diagnosis and phone number on a standard form. The calls reasons were recorded: appointments scheduling, medical issues or others. The alarming symptomes and signs requiring doctor advice or earlier appointments were checked on a short form: aggravating dyspnea, dysphagia, weakness or Raynaud's phenomenon, ulcerations, etc. Other issues, such as lumbar pain, joint pain, nausea, heartburn, etc requiring counselling, were registered as well. Results: Over 2 months, 280 calls from patients with rare rheumatologic diseases were received, out of which 171 (61%) were for scheduling or changing appointments. The rest were for medical advice regarding minor ailments, medication side effects, regular blood tests or other investigations performed after the last visit, issues regarding travelling etc. The triage nurses referred the patients to Emergency in 2 cases (0.7%), to the General Practitioner in 28 cases (10%) or planned an early appointment to the attending rheumatologist for medical issues in 20 cases (7.3%), briefed the attending physician in 94 cases (33%) and offered counselling in the other cases (49%), which included: medication side effects, analyses to be repeated, diet and promoting self-care. Conclusion: Telephonic calls, managed by experienced nurses, documented by standardized forms, are valuable additional tools in the management of rare inflammatory diseases. The pilot phone triage procedure improve patient's access to healthcare services. Periodic specialty training regarding rheumatologic emergency and communication skills increase the quality of this approach in rare diseases. References: [1] Thwaites C, Ryan S, Hassel A, Rheumatology (Oxford)2008; 47(4):522-5, Doi: 10.1093/rheumatology/ken041 [2] Fereira RO, Marques A, Cruz Mendes AMO, da Silva JA, Acta Reumatol Portuguesa2015; 40:163-8. Disclosure of Interests: None declared